Coordinating and programming multiple ROS-based robots with X-KLAIM - Bettini, Lorenzo; Bourr, Khalid; Pugliese, Rosario; Tiezzi, Francesco (International journal on software tools for technology transfer, 2023)
Software development for robotics applications is still a major challenge that becomes even more complex when considering multi-robot systems (MRSs). Such distributed software has to perform multiple cooperating tasks in a well-coordinated manner to avoid unsatisfactory emerging behavior. This paper provides an approach for programming MRSs at a high abstraction level using the programming language X-Klaim . The computation and communication model of X-Klaim , based on multiple distributed tuple spaces, permits coordinating with the same abstractions and mechanisms both intra- and inter-robot interactions of an MRS. This allows developers to focus on MRS behavior, achieving readable, reusable, and maintainable code. The proposed approach can be used in practice by integrating X-Klaim and the popular robotics framework ROS. We demonstrate the feasibility and effectiveness of our approach by (i) showing how it scales when implementing two warehouse scenarios allowing us to reuse most of the code when passing from the simpler to the more enriched scenario and (ii) presenting the results of a few experiments showing that our code introduces a slightly greater but acceptable latency and consumes less memory than the traditional ROS implementation based on Python code.